BDNF enhances spontaneous and activity-dependent neurotransmitter release at excitatory terminals but not at inhibitory terminals in hippocampal neurons - Shinoda, Yo; Ahmed, Saheeb; Ramachandran, Binu; Bharat, Vinita; Brockelt, David; Altas, Bekir; Dean, Camin (Frontiers in Synaptic Neuroscience, 2014)
Brain-derived neurotrophic factor (BDNF) is widely reported to enhance synaptic vesicle (SV) exocytosis and neurotransmitter release. But it is still unclear whether BDNF enhances SV recycling at excitatory terminals only, or at both excitatory and inhibitory terminals. In the present study, in a direct comparison using cultured rat hippocampal neurons, we demonstrate that BDNF enhances both spontaneous and activity-dependent neurotransmitter release from excitatory terminals, but not from inhibitory terminals. BDNF treatment for 5 minutes or 48 hours increased both spontaneous and activity-induced anti-synaptotagmin1 antibody uptake at excitatory terminals marked with vGluT1. Conversely, BDNF treatment did not enhance spontaneous or activity-induced uptake of anti-synaptotagmin1 antibodies in inhibitory terminals marked with vGAT. Time-lapse imaging of FM1-43 dye destaining in excitatory and inhibitory terminals visualized by post-hoc immunostaining of vGluT1 and vGAT also showed the same result: The rate of spontaneous and activity-induced destaining was increased by BDNF at excitatory synapses, but not at inhibitory synapses. These data demonstrate that BDNF enhances SV exocytosis in excitatory but not inhibitory terminals. Moreover, BDNF enhanced evoked SV exocytosis, even if vesicles were loaded under spontaneous vesicle recycling conditions. Thus, BDNF enhances both spontaneous and activity-dependent neurotransmitter release on both short and long time-scales, by the same mechanism.